The influence of thinking style and mental construal on consistency of consumer preferences - Aydın, Aslı Elif. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2012., 2012)
The objective of this dissertation is to investigate the role of two cognitive theories, namely dual process theory and construal level theory in influencing consumers’ evaluative processes and their consistency. For this purpose two experimental studies are conducted. The first study investigates the relationship between use of the experiential-rational systems and preference consistency. Findings demonstrate that affective stimuli induce more consistent preferences than analytical stimuli. Furthermore, it is shown that processing fluency is enhanced with the usage of experiential thinking and affective format compared to rational thinking and analytical format. Additionally, it is also shown that consistency of evaluations across consumers is improved when they relied on the rational system rather than the experiential system. The second study examines the relationship between mental construal level and preference consistency. Findings of this study reveal that when consumers adopt a high-level mental construal their evaluations become more consistent. Moreover, it is also shown that having matching high-level mental construals at two points in time rather than non-matching construals increases consistency of evaluations.
Keywords: Consumers' preferences.; Consumer behavior.